2005
DOI: 10.1016/j.gde.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial clefting: recent insights into a complex trait

Abstract: Orofacial clefts are common birth defects of multifactorial etiology. Several novel approaches have recently been applied to investigate the causes of clefts. These include examining Mendelian forms of clefting to identify genes that might also be implicated in isolated clefting, analyzing chromosomal rearrangements in which clefting is part of the resultant phenotype, studying animal models in which clefts arise either spontaneously or as a result of mutagenesis experiments, exploring how expression patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
168
1
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(180 citation statements)
references
References 75 publications
1
168
1
10
Order By: Relevance
“…Defects at any step of facial development can result in clefts of the lip or palate, which are common birth defects in humans, affecting between 1 in 500 and 1 in 1,000 births. Orofacial clefts occur as part of a syndrome or as isolated congenital defects and are though to be caused by a combination of genetic and environmental factors (reviewed in Jugessur and Murray, 2005;GritliLinde, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Defects at any step of facial development can result in clefts of the lip or palate, which are common birth defects in humans, affecting between 1 in 500 and 1 in 1,000 births. Orofacial clefts occur as part of a syndrome or as isolated congenital defects and are though to be caused by a combination of genetic and environmental factors (reviewed in Jugessur and Murray, 2005;GritliLinde, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They have a birth prevalence varying from 1 in 1,500 to 1 in 2,500 in Caucasian populations (Schutte and Murray 1999). These Wgures also depend on ethnic background, geographic origin, lifestyle factors and socioeconomic status (Jugessur and Murray 2005). OFC are most often classiWed into cleft lip with or without cleft palate (CL/P) and cleft palate only (CPO).…”
Section: Introductionmentioning
confidence: 99%
“…OFC are most often classiWed into cleft lip with or without cleft palate (CL/P) and cleft palate only (CPO). The etiology of OFC is complex, meaning both genetic and environmental factors are involved (Jugessur and Murray 2005;Krapels et al 2006a;Gritli-Linde 2007;Schliekelman and Slatkin 2002). Gene expression studies and a transgenic knock-out model with cleft phenotype have suggested that Msx1 is involved in the etiology of clefting (Satokata and Maas 1994;Davidson 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, neural tube defects are in decline due to folic acid supplementation but the frequency of orofacial clefts has stubbornly remained the same for decades (Kohut and Rusen, 2002). Most clefts are mostly nonsyndromic, in other words, they occur in isolation from other abnormalities (Jugessur and Murray, 2005). The causes are thought to be multifactorial, including an interaction between genes and the environment (Jugessur and Murray, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most clefts are mostly nonsyndromic, in other words, they occur in isolation from other abnormalities (Jugessur and Murray, 2005). The causes are thought to be multifactorial, including an interaction between genes and the environment (Jugessur and Murray, 2005). Clefts begin in embryogenesis and are a result of upper facial prominences that are smaller, have delayed growth or a different morphology.…”
Section: Introductionmentioning
confidence: 99%